Interaction Between Linepithema micans (Hymenoptera: Formicidae) and the Vine Mealybug Planococcus ficus (Hemiptera: Pseudococcidae): Trophobiosis or Predation? - Guindani, Aline Nobre; Nondillo, Aline; Pacheco da Silva, Vitor C.; Andzeiewski, Simone; Azevedo Filho, Wilson S. de; Bueno, Odair C. [UNESP]; Bolton, Marcos (Oxford Univ Press Inc, 2018)
The mealybug Planococcus ficus Signoret) Hemiptera: Pseudococcidae) has recently been detected in vineyards in southern Brazil. The ant Linepithema micans Forel) Hymenoptera: Formicidae) is the most abundant and frequent species in these vineyards, acting mainly as a disperser of the native soil scale, the ground pearl Eurhizococcus brasiliensis Wille) Hemiptera: Margarodidae). This study evaluated the interactions dispersal and predation) of L. micans with P. ficus. The first experiment evaluated the interaction between L. micans and P. ficus in a greenhouse, using Paulsen 1103 rootstock Vitis berlandieri x Vitis rupestris) planted in pots. Plants were infested by 1) adult females of P. ficus, and 2) adult females of P. ficus and L. micans, and all mealybugs remaining after the experimental period were counted. To evaluate P. ficus predation by L. micans, two laboratory experiments were conducted 25 degrees C, 80% relative humidity). In the first experiment, sprouted potatoes were infested with ovisacs, first-instar nymphs and adult females of P. ficus and evaluated in three treatments: 1) L. micans fed with carbohydrate and protein, 2) L. micans without food, and 3) without ants present. In the second, potatoes were infested only with first-instar nymphs of P. ficus and were exposed in two treatments: 1) L. micans without food, and 2) without ants present. The results were evaluated by counting the remaining mealybugs, with and without ants. The results showed that L. micans does not transport P. ficus, and predates on first-instar nymphs of the mealybug.
Keywords: mutualism; vine; predation